Carbon Dioxide in Lake Nyos, Cameroon, Estimated Quantitatively From Sound Speed Measurements - Boehrer, Bertram; Saiki, Kazuto; Ohba, Takeshi; Tanyileke, Greg; Rouwet, Dmitri; Kusakabe, Minoru (Frontiers in Earth Science, 2021)
Gases dissolved in the deep water of lakes can pose a hazard when extreme concentrations are reached. A sudden release of large amounts of gas can cost the lives of humans living in the neighbourhood, as happened at Lake Nyos in 1986. Since 2001, the gas risk at Lake Nyos has been mitigated by induced degassing, but the lake continues to be supplied by CO2, and a regular survey needs to be implemented to guarantee safe conditions. Frequent sampling of this remote lake requires an enormous effort, and many analytical techniques are very difficult to run at the lake site. In this contribution, we combined a commercially available sound speed sensor with a CTD (electrical conductivity, temperature, depth) probe to obtain an indirect but quantitative estimate of carbon dioxide concentrations with fine depth resolution (decimetre scale). Dissolved carbon dioxide increases sound speed but does not contribute to electrical conductivity. Hence the difference between measured and calculated (on the base of electrical conductivity, temperature and pressure) sound speed gives a quantitative indication of dissolved carbon dioxide. We infer the vertical distribution of dissolved CO2 and hence continue the survey of the progress of the intended degassing. In conclusion, we present an easy to implement method for very high CO2 concentrations in deep lakes, and we highly recommend the implementation of the sound speed-CTD probe combination at Lake Nyos and at other gas-laden volcanic lakes, as such an approach could safeguard the people living in the area with acceptable cost and effort for the operators. In this manner, alarming CO2 concentrations in deep parts of lakes can be detected in a timely fashion.